Cytokine levels in postmenopausal women depending on individual VDR, COL1A1, LRP5 gene polymorphisms - E. A. Maylyan (Медицинский вестник Юга России, 2018)
Objective: to study pro- and anti-infl ammatory cytokines serum levels at postmenopausal osteoporosis and their changes depending on separate polymorphic options of VDR, COL1A1 and LRP5 genes. Materials and methods: 180 postmenopausal women (60,0±0,77 years) were examined. Th e osteodensitometry was carried out by dual-energy x-ray absorptiometry method. Detection of 283 A>G (BsmI, rs1544410) polymorphisms of VDR gene, -1997 C>A (rs1107946) and 1546 (6252) G>T (Sp1 S>s, rs1800012) of COL1A1 gene, 3989 C>T (Ala1330Val, rs3736228) and 1999 G>A (Val667Met, rs4988321) of LRP5 gene was carried out by real-time PCR method. Enzyme-linked immunosorbent assay was used for defi nition of serum levels of interleukin (IL) -1β, -4, -6, -8, -10, -17A, tumor necrosis factor alpha (TNF-α), interferon gamma (INF-γ), osteoprotegerin (OPG), receptor activator of nuclear factor kappa-B ligand (RANKL). Results: it was established that women with postmenopausal osteoporosis had (P<0,05) increased serum IL-1-β, IL-8, IL-17A, TNF-α, RANKL concentration and decreased IL-4, IL-10 levels. Patients with GG genotype of rs1544410 polymorphism had also increased (P<0,05) IL-1-β, RANKL levels, OPG/RANKL index and decreased IL-10 values. Women with GT or TT genotypes of rs1800012 polymorphism of COL1A1 gene had (P<0,05) decreased IL-10, OPG values, OPG/RANKL index, but persons with CA or AA genotypes of rs1107946 polymorphism of COL1A1 gene had increased IL-4, IL-6, IL-8, IL-10, RANKL levels. IL-10 concentration decrease (P<0,05) was established for patients with GA genotype of rs4988321 polymorphism and CT or TT genotypes of rs3736228 polymorphism of LRP5 gene. Conclusion: the obtained data refl ect important pathogenetic aspects of postmenopausal osteoporosis and can be used for development of individualized treatment-and-prophylactic actions for women.